Critically important: The heterogeneous effect of politics on trade - Julian Hinz; Elsa Leromain (Kiel Institute for the World Economy (IfW), 2017)
The proliferation of international supply chains makes the domestic production of goods increasingly dependent on inputs from foreign sources. By expanding their sourcing portfolio to foreign suppliers, firms and by extension entire economies are more prone to the trade effects of adverse bilateral political shocks. In this paper, we analyze the relation between political relations and trade at lower levels of aggregation, allowing for a heterogeneous effect by types of inputs. We show that a negative shock to political relations has a more pronounced effect on trade of critical goods, conditional on the ease of switching suppliers. We construct a simple model exhibiting input-output linkages to clarify the mechanisms at play, from which we derive testable predictions. Using a new measure for countries' dependence on these critical inputs, we then test the proposed mechanism in a difference-in-differences framework. To address potential endogeneity issues we perform an event study, in which the treatment is an exogenous adverse political shock. Using a new dataset on the status of diplomatic representation and monthly trade data, we exploit the recalling or summoning of the ambassador of a country as a shock to bilateral political relations.
Keywords: F13; F14; F51; F52; 330; Trade frictions; Political Relations; Dependence; Input Sourcing